Challenges Faced by Teachers during Teaching Students with Developmental Disability at Primary School Level in Lahore - Zikra Faiz, Amna Arif, Shamasul Zia (JIE, 2024)
Purpose of this study was to examine the challenges faced by the teachers during teaching students who are intellectually disabled; suffering from Autism Spectrum Disorder, Learning Disability, and Attention Deficit and Hyperactivity Disorder (ADHD) at primary school level. The study was descriptive in nature and cross-sectional survey method was used to collect data. The sample of the study comprised of 258 (43 maleand 215 female) teachers from the special education institutes of Lahore district selected through proportionate stratified random sampling technique. A self-developed questionnaire comprising 14 closed-ended items was the research tool. The results of the study showed that teachers faced many problems during teaching. The majority of the participants face challenges during group activities, to control hyperactivity of the students and misbehavior of students. It is concluded that there was a significant difference between male and female teacher's perceptions about the challenges faced during teaching to developmental disable students. Furthermore, there was a significant difference in the perceptions of teachers regarding challenges faced during teaching students with developmental disabilities in term of teachers’ age and area of specialization. The study recommends pre-service and in-service teacher training was recommended.